A prospective study on the correlation between clinical outcome and residual prostatic adenoma weight ratio after transurethral resection of the prostate for benign prostatic hyperplasia - Rana, Y. P. S.; Swami, Yogesh K. (International Surgery Journal, 2022)
Background: Transurethral resection of the prostate (TURP) has been the most common surgical method for relieving symptoms of benign prostatic hyperplasia (BPH). However, there is no consent regarding the amount of tissue resected during TURP and it’s persuading on ruling of symptoms. Therefore the aim of the present study was to assess the correlation between clinical outcome and residual prostatic adenoma weight ratio after transurethral resection of the prostate for benign prostatic hyperplasia. Methods: A total of 70 patients presenting with obstructive/irritative lower urinary tract symptoms were evaluated for pre and post TURP values of prostatic weight, international prostate symptoms score (IPSS), postvoid residual volume (PVR), maximum flow rate (Q-max) and total prostate volume (TPV). Residual prostatic weight ratio (RPWR) was recorded in each case using transrectal ultrasound. Results: The effectiveness of TURP was 71.42%. On appraisal of the patients for IPSS, PVR, Q-max and TPV; the difference between pre-operative and post-operative values of these parameters was found to be statistically significant p<0.001. RPWR was found to be significantly lower (p<0.001) in patients who received valuable treatment. A strong linear correlation was found between total prostate and transition zone volumes in all groups. Conclusions: Values of IPSS, PVR, Q-max, TPV and operative parameters such as RPWR and residual prostatic weight are important parameters for the prediction of treatment outcome.